Full Thickness Burn Associated With Cutaneous Lymphoma Managed With Acellular Dermal Matrix: Case Report And Literature Review - Gaviria-Castellanos, Jorge Luis; Fayad-Lemaître, Federico; Duque-Bocanegra, Martha Liliana (European Journal of Applied Sciences, 2024)
Objective: To perform a literature review of patients that presented burns associated with previous malignant skin neoplasms, and to report the clinical case of a patient with a diagnosis of 2 types of cutaneous T lymphoma who also presented a chemical burn. Likewise, to evaluate the postoperative functional and aesthetic results after the reconstruction of the injured tissue with a monolayer acellular dermal matrix (Integra®) and partial skin grafts, in the same surgical time. Methods: A descriptive observational study of a case report type and narrative literature review was carried out. The case report is presented thoroughly and the literature review was made in databases with a combination of MeSh terms. Results: No reports of cases of burns associated with cutaneous lymphoma were found in the literature. The proposed surgical management was successful, in which the dermal matrix and skin grafts integrated completely, an aesthetic and functional outcome was achieved, and no functional limitations of the limb were evident during the postoperative period. Conclusions: The treatment of burns in patients who previously have a malignant cutaneous disorder is aimed at surgical debridement and reconstruction of the skin coverage with partial skin grafts, as soon as possible. The use of a dermal matrix reduces the possibility of scar complications. As far as we could verify, this is the first time that a burn has been reported on skin previously affected with two lymphoma-type skin neoplasms managed with a dermal matrix, concluding that the neoplasm does not affect dermal matrix integration.